Tăng cường quản lý công tác kiểm tra, đánh giá kết quả học tập nhằm nâng cao năng lực tự học của sinh viên - Phạm , Thị Thu Thủy (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TÂN TRÀO, 2021)
Ability development is an important solution to improve the quality of training. Self-study ability is an important element, helping students achieve good results in learning. Therefore, in this article, the author mentions the solution: Strengthening the examination and evaluation of students' learning results in order to raise the student's self-learning ability.